Metamaterial‐Enabled Hybrid Receive Coil for Enhanced Magnetic Resonance Imaging Capabilities - Xia Zhu; Ke Wu; Stephan W. Anderson; Xin Zhang (Advanced Science)
Abstract Magnetic resonance imaging (MRI) relies on high‐performance receive coils to achieve optimal signal‐to‐noise ratio (SNR), but conventional designs are often bulky and complex. Recent advancements in metamaterial technology have led to the development of metamaterial‐inspired receive coils that enhance imaging capabilities and offer design flexibility. However, these configurations typically face challenges related to reduced adaptability and increased physical footprint. This study introduces a hybrid receive coil design that integrates an array of capacitively‐loaded ring resonators directly onto the same plane as the coil, preserving its 2D layout without increasing its size. Both the coil and metamaterial are individually non‐resonant at the targeted Larmor frequency, but their mutual coupling induces a resonance shift, achieving a frequency match and forming a hybrid structure with enhanced SNR. Experimental validation on a 3.0 T MRI platform shows that this design allows for adjustable trade‐offs between peak SNR and penetration depth, making it adaptable for various clinical imaging scenarios.